Evaluation of Tenaga Nasional Berhad payment kiosk / Nadirah Rahmat - Rahmat, Nadirah (2016)
Self-service payment kiosks are now widely used in Malaysia including at Tenaga Nasional Berhad (TNB). This payment kiosks become required for TNB to shorten the time of counter services. Hence Tenaga Nasional Berhad is applying this payment kiosk in order to improve customer experience and to gain trust. However, TNB Payment Kiosk has provided difficulty to the user with several issue such unable to display updated bill amount, no sound and alert when performing a transaction. Users are from various age groups and background which involve a lot in customer relationship. This study is related to usability and this issues is to provide the evaluation of the kiosks. This study also has developed the usability model for evaluation that contains seven factors. With the evaluation has been conducted, recommendations are provided after the issues have been identified so that developers can make enhancement to the system. This will help to improve the payment kiosks are implemented at TNB and enhance the Tenaga Nasional Berhad productivity in the customer service area.